Glimpses of Piwong Ifugao 'Alim, 1975 - Del Rosario, Rosario de Santos (UP Diliman, 2003)
"An audio-visual presentation accompanying the dissertation "The Ifugao 'Alim' as Gendered Discourse"." -- in CD-ROM.